2012
DOI: 10.1016/j.taap.2011.12.015
|View full text |Cite
|
Sign up to set email alerts
|

PCB153 reduces telomerase activity and telomere length in immortalized human skin keratinocytes (HaCaT) but not in human foreskin keratinocytes (NFK)

Abstract: Polychlorinated Biphenyls (PCBs), ubiquitous environmental pollutants, are characterized by long term-persistence in the environment, bioaccumulation, and biomagnification in the food chain. Exposure to PCBs may cause various diseases, affecting many cellular processes. Deregulation of the telomerase and the telomere complex leads to several biological disorders. We investigated the hypothesis that PCB153 modulates telomerase activity, telomeres and reactive oxygen species resulting in the deregulation of cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 68 publications
0
25
3
Order By: Relevance
“…Our results are inconsistent with the findings of prior in vitro studies that observed telomere shortening because of exposure to PCB 153, PCB 126, PCB 52, PCB 28, or 2-(4â€Č-chlorophenyl)-1, 4-benzoquinone (PCB3pQ) (Jacobus et al, 2008; Senthilkumar et al, 2011; Senthilkumar et al, 2012; Xin et al, 2016; Ziegler et al, 2016). Alternative mechanisms by which PCBs may induce telomere lengthening have been proposed (Scinicariello and Buser, 2015).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results are inconsistent with the findings of prior in vitro studies that observed telomere shortening because of exposure to PCB 153, PCB 126, PCB 52, PCB 28, or 2-(4â€Č-chlorophenyl)-1, 4-benzoquinone (PCB3pQ) (Jacobus et al, 2008; Senthilkumar et al, 2011; Senthilkumar et al, 2012; Xin et al, 2016; Ziegler et al, 2016). Alternative mechanisms by which PCBs may induce telomere lengthening have been proposed (Scinicariello and Buser, 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…In vitro , immortalized human skin keratinocytes, hamster lung fibroblasts, immortalized lymphocytes, or human promyelocytic leukemia cells exposed to PCB 153, PCB 126, PCB 52, PCB 28, or 2-(4â€Č-chlorophenyl)-1, 4-benzoquinone (PCB3pQ), have shortened telomeres (Jacobus et al, 2008; Senthilkumar et al, 2011; Senthilkumar et al, 2012; Xin et al, 2016; Ziegler et al, 2016). Conversely, PCB 138 and PCB 153 upregulate c- myc in vitro (Ghosh et al, 2007; Gribaldo et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…ROS are also able to reduce telomerase activity which can determine telomere shortening. The contribution of all or part of these alterations may facilitate the onset of tumors and more specifically HCC [200][201][202][203][204][205] . At present we have no conclusive data on the relationship between PCBs and HCC and further studies will be needed to establish the causal link.…”
Section: Polychlorinated Biphenylsmentioning
confidence: 99%
“…Several studies investigating telomere dynamics in PCB-exposed individuals or PCB-treated telomerase positive tumor cell lines have been published (Xin et al 2016; Jacobus et al 2008; Shin et al 2010; Senthilkumar et al 2011, 2012; Mitro et al 2015). Whereas in two population-based studies low dose exposure to non-ortho PCBs was associated with longer TL in leukocytes (Shin et al 2010; Mitro et al 2015), long-term treatment of cell lines with PCBs resulted in cell-type and PCB congener-specific adverse effects on TL, htert activity and expression of telomere-associated shelterin genes (Xin et al 2016; Jacobus et al 2008; Senthilkumar et al 2011, 2012). Based on these recent findings, we selectively analyzed TL of granulocytes and lymphocytes in peripheral blood from individuals occupationally exposed to very high levels of PCBs.…”
Section: Introductionmentioning
confidence: 99%